Microencapsulated organic coconut oil as a natural phase change material for thermo-regulating cellulosic fabrics - ÖNER, ERHAN; KAHRAMAN, MEMET VEZİR (SPRINGER, 2019)
In this work, coconut oil was utilized as a natural phase change material (PCM) and applied on cellulosic fabrics for thermo-regulation. Organic coconut oil was microencapsulated in melamine formaldehyde and poly (methyl methacrylate) polymer shells by in situ and suspension polymerization methods, respectively. The fabricated microcapsules were applied on a daily wear stretch denim fabric and a cotton shirting fabric by knife-coating to impart thermo-regulation functionality. The microencapsulated PCMs and the treated fabric samples were characterized using Fourier transform infrared spectroscopy, differential scanning calorimetry, thermal gravimetric analysis and scanning electron microscopy. The results indicated that latent heats of 81.9 J/g and 39.1 J/g at melting peak temperatures of 21.5 degrees C and 22.1 degrees C were successfully achieved with the microencapsulated PCMs which enabled the fabrics to possess remarkable latent heats in between 6.7 and 14.9 J/g. Graphic abstract
Keywords: Phase change material; Coconut oil; Microencapsulation; Thermo-regulation; Cellulosic fabric; Thermal energy storage; TEXTILE MATERIALS; MICROCAPSULES; PERFORMANCES; PCM